2018
DOI: 10.21470/1678-9741-2017-0164
|View full text |Cite
|
Sign up to set email alerts
|

Are Pre and Postoperative Platelet to Lymphocyte Ratio and Neutrophil to Lymphocyte Ratio Associated with Early Postoperative AKI Following CABG?

Abstract: ObjectiveIn this study, we investigated the role of two of the recent biomarkers of inflammation on the development of acute kidney injury in the early postoperative period of isolated coronary artery bypass grafting.MethodsThree hundred and eleven patients, who underwent isolated coronary artery bypass grafting with cardiopulmonary bypass by the same surgery team in our clinic between May 2010 and October 2014, who had a preoperative serum creatinine level lower than 1.5 mg/dl were included in the study. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 23 publications
3
48
1
1
Order By: Relevance
“…In the setting of cardiac surgery, Parlar et al also demonstrated that an elevated preoperative PLR was associated with early postoperative AKI [OR 1.06 (1.01–1.10), p = 0.01] [66]. The cut-off value to predict AKI determined in this study was 136.85, which demonstrated a sensitivity of 71.0% and specificity of 70.7% [66].…”
Section: Complete Blood Count Parameters and Akimentioning
confidence: 67%
See 1 more Smart Citation
“…In the setting of cardiac surgery, Parlar et al also demonstrated that an elevated preoperative PLR was associated with early postoperative AKI [OR 1.06 (1.01–1.10), p = 0.01] [66]. The cut-off value to predict AKI determined in this study was 136.85, which demonstrated a sensitivity of 71.0% and specificity of 70.7% [66].…”
Section: Complete Blood Count Parameters and Akimentioning
confidence: 67%
“…In a retrospective cohort of 590 patients undergoing cardiovascular surgery, postoperative elevated NLR was significantly associated with an increased risk of postoperative AKI and mortality [65]. Parlar et al also demonstrated that an increased NLR was associated with postoperative AKI in patients undergoing cardiovascular surgery with cardiopulmonary bypass [66]. An elevated preoperative NLR was also documented as a predictor of AKI in burn surgery patients, in whom a cut-off value of 11.7 was optimal for postoperative AKI prediction (OR 1.094 (1.064–1.125), p < 0.001) [67].…”
Section: Complete Blood Count Parameters and Akimentioning
confidence: 99%
“…Thus, the tendency to search for an inexpensive and easy-to-use biomarker is observed, increasing interest in "old biomarkers" such as C-reactive protein, neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR). This trend may be noted in recent publications in the Brazilian Journal of Cardiovascular Surgery (BJCVS) [4] .…”
Section: Bjcvs Highlightmentioning
confidence: 64%
“…A recent paper published in Brazilian Journal of Cardiovascular Surgery (BJCVS) introduces platelet to lymphocyte ratio (PLR) and neutrophil to lymphocyte ratio (NLR) as two novel index to predict development of postoperative acute kidney injury (AKI) of isolated coronary artery bypass grafting [1] . This case-control study included a wide range of patients with AKI ( i.e .…”
mentioning
confidence: 99%